Toward National Broadband Equality: The Role of 5G Fixed Wireless Access in Indonesia - Agung Setiaji; Deiny Mardian; Lydia Sari (Publica Scientific Solution, 2026)
This research analyzes the role of Fifth Generation Fixed Wireless Access (5G FWA) in supporting broadband equity in Indonesia as a developing archipelagic country facing geographical challenges and digital infrastructure inequality. The research aims to evaluate the potential of hybrid fiber-wireless broadband architecture as a solution to accelerate broadband expansion, particularly in rural, remote, and underserved areas. The research employed a qualitative-descriptive approach combined with techno-economic analysis and policy studies, along with a comparative analysis between Fiber to the Home (FTTH) and 5G FWA based on deployment flexibility, scalability, implementation speed, and suitability to archipelagic geographical conditions. The findings indicate that 5G FWA offers significant advantages in accelerating broadband deployment in areas with high geographical barriers through more flexible infrastructure compared to full FTTH deployment. The hybrid fiber-wireless architecture enables the integration of the national fiber optic backbone with last-mile wireless connectivity to improve broadband access in rural and island regions. The success of broadband equity is influenced not only by technological capabilities but also by spectrum policy support, infrastructure sharing, investment incentives, and digital literacy programs, with the integration of Massive MIMO and beamforming technologies contributing to improved coverage efficiency and capacity. This study concludes that 5G FWA should be positioned as a complementary broadband solution rather than a complete replacement for fiber optic infrastructure, with the hybrid approach offering a more realistic, flexible, and scalable implementation pathway to reduce the digital divide and support national digital transformation in Indonesia.